Contribution of Microbiota to Bioactivity Exerted by Bee Bread - Nikos Asoutis Didaras; Ioanna Karaiskou; Marios Nikolaidis; Christina Siaperopoulou; Irini Georgi; Christina Tsadila; Katerina Karatasou; Grigoris D. Amoutzias; Dimitris Mossialos (MDPI AG, 2024)
Bee-collected pollen (BCP) and bee bread (BB) are honey bee products known for their beneficial biological properties. The main goal of this study was to investigate BB microbiota and its contribution to bioactivity exerted by BB. The microbiota of BB samples collected at different maturation stages was investigated via culture-independent (Next Generation Sequencing, NGS) and culture-dependent methods. Microbial communities dynamically fluctuate during BB maturation, ending in a stable microbial community structure in mature BB. Bee bread bacterial isolates were tested for phenotypes and genes implicated in the production and secretion of enzymes as well as antibacterial activity. Out of 309 bacterial isolates, 41 secreted hemicellulases, 13 cellulases, 39 amylases, 132 proteinases, 85 Coomassie brilliant blue G or R dye-degrading enzymes and 72 Malachite Green dye-degrading enzymes. Furthermore, out of 309 bacterial isolates, 42 exhibited antibacterial activity against Staphylococcus aureus, 34 against Pseudomonas aeruginosa, 47 against Salmonella enterica ser. Typhimurium and 43 against Klebsiella pneumoniae. Artificially fermented samples exerted higher antibacterial activity compared to fresh BCP, strongly indicating that BB microbiota contribute to BB antibacterial activity. Our findings suggest that BB microbiota is an underexplored source of novel antimicrobial agents and enzymes that could lead to new applications in medicine and the food industry.